2021
DOI: 10.3390/molecules26195898
|View full text |Cite
|
Sign up to set email alerts
|

Toxics or Lures? Biological and Behavioral Effects of Plant Essential Oils on Tephritidae Fruit Flies

Abstract: The family Tephritidae (Diptera) includes species that are highly invasive and harmful to crops. Due to globalization, international trade, and human displacement, their spread is continuously increasing. Unfortunately, the control of tephritid flies is still closely linked to the use of synthetic insecticides, which are responsible for detrimental effects on the environment and human health. Recently, research is looking for alternative and more eco-friendly tools to be adopted in Integrated Pest Management (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 231 publications
(351 reference statements)
1
21
0
Order By: Relevance
“…Toxic effects of limonene and EOs containing high proportions of limonene were previously reported for tephritid species, including A. fraterculus (Salvatore et al, 2004;Papachristos et al, 2009;Ruiz et al, 2014;Papanastasiou et al, 2017;Oviedo et al, 2018Oviedo et al, , 2020, where survival, emergence, and fecundity were affected by exposure to these phytochemicals. In agreement, Ruiz et al (2021) have found that only the EO of lemon, as opposed to the EOs of orange and grapefruit, was able to stimulate A. fraterculus males. Among these three EOs, lemon EO had the lowest R-limonene concentration (Ruiz et al, 2015;González-Mas et al, 2019).…”
Section: Frontiers In Ecology and Evolutionsupporting
confidence: 73%
“…Toxic effects of limonene and EOs containing high proportions of limonene were previously reported for tephritid species, including A. fraterculus (Salvatore et al, 2004;Papachristos et al, 2009;Ruiz et al, 2014;Papanastasiou et al, 2017;Oviedo et al, 2018Oviedo et al, , 2020, where survival, emergence, and fecundity were affected by exposure to these phytochemicals. In agreement, Ruiz et al (2021) have found that only the EO of lemon, as opposed to the EOs of orange and grapefruit, was able to stimulate A. fraterculus males. Among these three EOs, lemon EO had the lowest R-limonene concentration (Ruiz et al, 2015;González-Mas et al, 2019).…”
Section: Frontiers In Ecology and Evolutionsupporting
confidence: 73%
“…The utilization of machine learning, artificial intelligence and brain–computer interfaces for fragrance design, synthesis and quantitative olfactory studies is expected to show rapid growth [ 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. The safety, therapeutic efficacy, allergic effect and biodegradability of these new fragrances should also be investigated further, especially in the case of fragrances containing new scaffolds [ 174 , 175 , 176 , 177 , 178 , 179 , 180 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several recent studies, plant essential oils (EOs) have been shown to have antifungal, antimicrobial, cytostatic, and insecticidal properties [ 14 , 15 ]. Essential oils are natural combinations of chemicals with low molecular weight, volatility, and lipophilic nature found in various plant families, including Asteraceae, Apiaceae, Lamiaceae, Myrtaceae, Lauraceae, and Rutaceae [ 15 , 16 ]. Essential oil components (EOCs) are classified into four classes according to their chemical structure: terpenes, terpenoids, phenylpropenes, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oil components (EOCs) are classified into four classes according to their chemical structure: terpenes, terpenoids, phenylpropenes, and others. They may also contain a diversity of functional groups such as hydrocarbons (monoterpenes, sesquiterpenes, and aliphatic hydrocarbons); oxygenated compounds (monoterpene and sesquiterpene alcohols, aldehydes, ketones, esters, and other oxygenated compounds); and sulphur and nitrogen-containing compounds (thioesters, sulfides, isothiocyanates and nitrile) [ 15 , 16 , 17 ]. Components of essential oils exert their activities (mode of action) on pests in a neurotoxic way, for example, like gamma-aminobutyric acid (GABA), insect growth regulator (IGR), octopamine synapses (OS), impending digestive enzymes, inhibition of glutathione S-transferase (GST), cytochromes P450 (CYPs), and acetylcholinesterase (AchE) inhibitors for effective control in pre-and post-harvest agricultural techniques [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation